VALORIZATION OF THE PYRITE IN VIEW OF THE SYNTHESIS OF FERRATE OF POTASSIUM AND SULPHATE FERRIC WALL LAMPS IN THE TREATMENT OF THE DRINKING WATERS - de Dieu, Ramaroson Jean; Oliva, Andrianaivoravelona Jaconnet; Rijalalaina, Rakotosaona (IJRDO-Journal of Applied Science, 2017)
Pyrite FeS2 chemical formula is part of iron ore abundantly found in Madagascar. It also presents many application that a few of them are the goal of this work. The synthesis of ferric sulfate from pyrite is a simple and convenient method (cost, time, etc.) while that of ferric oxide, to serve the completion of the synthesis of ferrate, is a bit complicated. The synthesis of ferrate alkaline VI is an easy process, but requires a lot of control. It shows positive results only in a temperature above 800 °C over 3 hours time. Below this temperature we got another product with low oxidative we named ferrate IV or V. The application of these reagents in water treatment reveals the advantage of ferrate which is at the same time coagulant and disinfectant and ferric sulfate is cationic coagulant and a flocculent proven by its power to form large flocks.